2010
DOI: 10.1109/tnano.2009.2017019
|View full text |Cite
|
Sign up to set email alerts
|

Numerically Efficient Modeling of CNT Transistors With Ballistic and Nonballistic Effects for Circuit Simulation

Abstract: Abstract-This paper presents an efficient carbon nanotube (CNT) transistor modeling technique which is based on cubic spline approximation of the non-equilibrium mobile charge density. The approximation facilitates the solution of the selfconsistent voltage equation in a carbon nanotube so that calculation of the CNT drain-source current is accelerated by at least two orders of magnitude. A salient feature of the proposed technique is its ability to incorporate both ballistic and nonballistic transport effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 30 publications
0
62
0
Order By: Relevance
“…Again, E vh1 and E vh2 being Van Hove Singularity [9][10][11][12][13][14][15][16][17][18]24] energies where DOS is real and finite to be:…”
Section: Analytical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Again, E vh1 and E vh2 being Van Hove Singularity [9][10][11][12][13][14][15][16][17][18]24] energies where DOS is real and finite to be:…”
Section: Analytical Modelmentioning
confidence: 99%
“…Having strong carbon-carbon bond in the planar honeycomb structure of graphite [9], the modulus of elasticity at its basal plane is superior than most of the materials known has proved itself trustworthy as per their fabrication is concerned. Near ballistic transport [14,15] of mobile carriers through the CNT channel can be observed with the absence of dangling bonds. In this paper, keeping channel length 20 nm and taking diameter of nanotube 1.5 nm for optimum transport, we have analytically modeled COI/CON devices [19] influenced with quantum mechanical [16,[20][21][22][23] effects as dimensions can be compared with the De-Broglie wavelength.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This model is based on cubic spline approximation of non-equilibrium mobile charge density, where approximations were made to solve for the self-consistent voltage originally defined as a non-linear function of terminal capacitance reducing the cost of the number of Newton-Raphson iterations needed [14]. Consequently, the model was developed to get around the main stumbling block in circuit-compatible modeling for CNTFETs, supplemented by the fact that accurate calculations for mobile charges inherently involve numerical integration of the DOS (density of states) given by Eqs.…”
Section: Model Analysismentioning
confidence: 99%
“…In recent years, ongoing research endeavors have revealed a number of CNTFET computer models that are compatible with SPICE that helps a great deal in evaluating delays, estimating power requirements and simulating any performance degradation. Further, it makes multiple transistor circuit simulations more viable [10][11][12][13][14][15].…”
mentioning
confidence: 99%